Pengaruh Good Corporate Governance, Corporate Social Responsibility dan Kepemilikan Manajerial terhadap Kinerja Keuangan Perusahaan Food and Beverage di Indonesia - Sofiana Hidayah; Taufik Kurniawan; Yuli Kurniawati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
This study investigates the impact of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Managerial Ownership on the financial performance of food and beverage companies in Indonesia. Financial performance is assessed using Return on Assets (ROA), while GCG and CSR are measured based on the Global Reporting Initiative (GRI) 4.0 indicators. Managerial Ownership is determined by the percentage of shares held by members of the board of commissioners, directors, and managers. This quantitative research includes food and beverage companies listed on the Indonesia Stock Exchange from 2021 to 2023. The sample, consisting of 126 data points from 42 companies, was selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS. The findings reveal that Good Corporate Governance and Corporate Social Responsibility do not have a significant effect on financial performance, whereas Managerial Ownership has a significant positive effect. However, when combined, Good Corporate Governance, Corporate Social Responsibility, and Managerial Ownership collectively influence the financial performance of food and beverage companies in Indonesia..